New additions to the leafhopper genus Salka Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae) from Hainan and Henan Provinces of China - Song, Yue-Hua; Li, Zi-Zhong (Zootaxa, 2016)
The leafhopper genus Salka Dworakowska, 1972 belongs to the Typhlocybinae tribe Erythroneurini with Zygina nigricans Matsumura, 1932 as its type species. The known species of this genus are distributed in the Oriental and Palearctic regions. Recently, it was reviewed by Zhang et al. (2009), Ohara (2012) and Song & Li (2012). Seventy-eight species are known, including 36 species from China. In this present work, two new species from China are described and illustrated. All specimens examined are deposited to the collection of the Institute of Entomology, Guizhou University, China (GUGC).